A Comparative Study of Beauty and its Relation to Pleasure and Goodness in the Philosophy of Plotinus and Avicenna - Muḥammūd Ṣeydiī; Ḥusayn Zamānīhā (آموزه‌‌های فلسفه اسلامي, 2024)
The truth and nature of beauty, as a secondary intelligible (Arabic: مَعْقولُ الْثَّانی, romanized: maʿqūl al-thānī), have become a topic of discussion among philosophers. In the present study, employing an analytical-comparative method, the truth of beauty and its relationship with pleasure and goodness from the perspectives of Plotinus and Avicenna (Arabic: إبْن سینا, romanized: Ibn Sīnā) are examined. It is demonstrated that the thoughts of these two philosophers, despite foundational differences in their metaphysical bases, have significant similarities in this specific area. Although Plotinus recognizes a specific role for proportion and symmetry in the beauty of sensible things influenced by the Platonic tradition, he does not consider this to be the cause or the main criterion of beauty. Instead, he seeks the criterion of sensible beauty among its intelligible causes, with the absolute Good or goodness at the forefront, and regards sensible beauty as a shadow of intelligible beauty. Although Avicenna does not believe in the theory of exemplarism (exemplary ideas), he believes that the cause and criterion of beauty is the perfection of a being. According to Ibn Sina, both beauty itself and the power to perceive beauty are rooted in the perfection of existence. Therefore, the Intellects (Arabic: عُقول, romanized: ʿAqūl), which are above the sensible world (the sensible world), possess a higher degree of beauty, and the Necessarily-Existing (Arabic: واجِبُ الْوُجُود, romanized: Wājib al-Wujūd, lit.: Necessary Being), which is absolute perfection, is at the pinnacle of beauty and grandeur, while at the same time possessing the most complete perception of beauty.